TEKNIK MUHASABAH PERSPEKTIF AL QUR’AN DALAM SURAT AL INSYIRAH AYAT 1 – 8. - Erlindawati Erlindawati; Hasan Zaini; Irman Irman (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2025)
In human life, of course, there is no escape from mistakes. The existence of an incident makes the hearts of all people on earth become anxious and worried about the behavior they will do when undergoing an activity. This can dig oneself to always make peace before or after doing something that is done. In this study has the aim to describe the muhasabah technique of the Qur'anic perspective contained in surah Al Inshirah verses 1-8. Muhasabah has a positive effect on all individuals to always be vigilant and as a form of self-assessment. In this study, the author uses a qualitative approach with a descriptive method of analysis through library research techniques by collecting data or materials related to discussions and problems, taken from literature sources, then analyzed. From some of the results of research conducted by previous researchers show that muhasabah activities are one of the good techniques carried out in introspection, self- evaluation, calming down or improving themselves and reinforced by the perspective of Surat Al Insyirah which contains the meaning of sincerity, patience and hard work and if you practice this letter it will get spaciousness in life, Get ease in finding sustenance,Get spaciousness of heart.